Money laundering risk in developing and transitive economies: Analysis of cyclic component of time series - Valentyna Levchenko; Anton Boyko; Victoria Bozhenko; Serhii Mynenko (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
Money laundering has become a global threat to the international stability and security, leading both to economic and social upheavals, and to an increase in terrorist threats. Therefore, an objective necessity arises for a more detailed study of the money laundering within the scope of its developmental patterns and time-dependent behaviour. The study mission is the development of a theoretical framework and methodological support for modelling the cyclic component of the money laundering risk. The correlation and regression are used for isolating the cyclic component. In turn, the Fourier harmonic analysis allows specifying the cyclic component. Additionally, we carried out a decomposition of time series, analysis of its volatility and persistence using the Hurst exponent. We determined the peaks, downturns and duration of the money laundering cycles in the developed economies and economies in transition, and established the possibility of predicting this process in the medium term. We proved the internationalization of the money laundering and the similarity of behaviour of trends that characterize it both for developed economies among themselves and between groups of countries. The further scientific research is needed within the framework of the imposition of trends in the development of the money laundering processes of some countries on others and the formation of international medium-term anti-fraud strategies.
Keywords: G32; C22; O17; 650; anti money laundering; money laundering risk; time series analysis; trend analysis; cyclic component; Fourier analysis; volatility; persistence